SGLT2 inhibitors in autoimmune diseases: emerging therapeutic potential and clinical challenges - Luo, Taimin; Zhang, Liaoyun; Tu, Kun; Li, Gen; Su, Hao; Gong, Guanli; Huang, Yilan; Li, Min; Yang, Xuping (Frontiers in Immunology, 2025)
Autoimmune diseases (AIDs) are conditions where the immune system mistakenly attacks self-antigens, leading to tissue and organ damage. The exact mechanisms underlying AIDs pathogenesis remain unclear, and effective treatments are currently limited, posing significant therapeutic challenges. Recent studies suggest that targeting T cell immune metabolism could be a promising approach for treating AIDs. Repurposed type 2 diabetes mellitus (T2DM) medications, which modulate immune metabolic processes, have shown potential in various inflammatory conditions. Sodium-glucose cotransporter-2 (SGLT2) inhibitors, a novel class of oral antidiabetic agents, not only regulate metabolic dysfunction but also offer protective effects on the heart and kidneys. Emerging preclinical evidence indicates that SGLT2 inhibitors possess immunomodulatory properties, highlighting their potential in enhancing T cell-mediated autoimmune therapy. Clinical studies further validate that SGLT2 inhibitors significantly reduce the risk of chronic kidney disease (CKD) progression in non-diabetic patient groups, such as those with chronic glomerulonephritis like IgA nephropathy. This review aims to evaluate current preclinical and clinical research on the impact of SGLT2 inhibitors on the immune system and explore their mechanisms of action relevant to treating AIDs.